(untitled) (Economic and Political Thought, 2013)
The article is an attempt to answer a question what the role of the Euro- -Atlantic system in the multi-polar world will be and if it will be able to safeguard peace and security in the world. Will it be able to compete with the growing super-powers of China, India, Russia and other emerging powers? The author presents a thesis that it is very difficult to answer those questions today because the world is becoming less and less predictable and the dynamic of changes is unprecedented. Additionally, it remains in the shade of the still existing financial and economic crisis and it is hard to say when it is going to finish and what the consequences for the USA, the European Union and other participants of the international relations will be. The author demonstrates that a new, multi-polar and multi-civilization world order is being created today, and the period between 1991 and 2010 proves that the Atlantic Community was not prepared for the collapse of the bipolar order and the Soviet Empire, which was believed to be the greatest threat for the international peace and security. Moreover, the author considers whether a renaissance of the Atlantic Community is possible and whether it could play the same role in the 21st century as it used to play under the leadership of the USA in the late 20th century. He suggests that if the Atlantic Community overcomes the present impasse, it will be a co-author of a new international multi-polar order. However, if it does not, the world will face a chaos, conflicts and wars for years because China or India will not be strong enough for several or even dozens of years to create a new peaceful international order without or with the marginalized Atlantic Community.